2019
DOI: 10.1111/are.14277
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on nutrient composition and quality evaluation in a new variety and wild‐typed ridgetail white prawn ( Exopalaemon carinicauda )

Abstract: Kesuhong No. 1 with high concentration of astaxanthin was a newly approved aquaculture variety of ridgetail white prawn (Exopalaemon carinicauda) in China, and the information on the nutrient composition and quality evaluation of this new variety is insufficient. Thus, the proximate composition, amino acid and fatty acid profiles were analysed and compared between the new variety and the wild‐typed prawn in the present study, for its better application of the new variety. It showed that there were no significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Similarly, Hoang et al (2018) reported that grey mullet could be co-cultured with white shrimp at the fish stocking density of 10% shrimp biomass to improve water quality, overall productivity and nutrient utilization efficiency. It is worth noting that the ridgetail white shrimp Exopalaemon carinicauda is one of the vital economic species, of which the rearing area has been rapidly expanding for the past few years (Zhang et al, 2019). To date, E. carinicauda has contributed one-third of the total production of polyculture ponds in eastern China .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Hoang et al (2018) reported that grey mullet could be co-cultured with white shrimp at the fish stocking density of 10% shrimp biomass to improve water quality, overall productivity and nutrient utilization efficiency. It is worth noting that the ridgetail white shrimp Exopalaemon carinicauda is one of the vital economic species, of which the rearing area has been rapidly expanding for the past few years (Zhang et al, 2019). To date, E. carinicauda has contributed one-third of the total production of polyculture ponds in eastern China .…”
Section: Introductionmentioning
confidence: 99%